Toxicidad aguda y actividad antioxidante de los extractos de hojas y tallo de Senna quinquangulata - Reátegui Nicolini, Xusan Elmira (2023)
Objective: Determine the acute toxicity and antioxidant activity of the leaf and stem extracts of Senna quinquangulata. Methodology: Leaves and stem collected for convenience, being used in the preparation of alcoholic and hydroalcoholic extracts to evaluate acute toxicity at 10, 100 and 1000 ppm in nauplii of Artemia franciscana; methanolic extract to evaluate antioxidant activity by the DPPH method tested at 1, 10, 25 and 50 mg/mL. Results: the acute toxicity test showed that all the extracts evaluated have an LC50 > 1000 ppm and, therefore, were not considered toxic. In antioxidant activity, the methanolic extracts of leaves and stem of S. quinquangulata present a percentage of inhibition greater than 50% at concentrations of 25 and 50 mg/mL. Conclusion: The methanolic extract of S. quinquangulata - leaves obtained an IC50=13.42 mg, being the one with the best antioxidant activity.